Numerical Modeling of Thermal Processes while Depositing Layers in Additive Production - Kuznetsov M. A. Maksim Aleksandrovich; Krampit M. A. Maksim Andreevich; Kryukov A. V. Artem Viktorovich; Kust T. S. Tatiana Sergeevna; Pavlov N. V. Nikolay Viktorovich (2018, 2018)
Title screen